RE-EDUCATION: A TREATMENT TO REVISE THE MISUNDERSTANDING OF TERRORIST RELIGION, A STUDY CASE ON FIRST FEMALE TERRORIST IN INDONESIA - Sri Sulistjaningsih; Latifah Mukhlasin (Social Welfare Study Program, 2019)
Abstract. Terrorism itself began to become one of the global issues that was quite important and often became the focus of the international community. The terrorism ideology had spread out in all country in the world. In 2016, Indonesian society was shocked by women who would be candidate of suicide bomber attack. One of them named Dian Yulia Novi, the first woman involved in a terrorist act and ready to become a suicide bomber to attack the State Palace of Indonesia by carrying a pot bomb with a high enough explosive power. This study uses descriptive qualitative research method while the type of research uses a case study. Now, Dian is undergoing her sentences in Correctional for Women Class IIA Bandung. Dian’s suicide bombing case is rare and need special treatment to decrease her radicalism ideology. So, the correctional institution and National Counterterrorism Agency provide reeducation program for her treatment during her imprisonment to give the right understanding about Islam and prove that her ideology is wrong. The development from the treatments program that has been obtained is she not trying to spread his views on radicalism, and she willing to associate with prisoners of other cases even though with a limited people. Abstrak. Terorisme sendiri mulai menjadi salah satu masalah global yang cukup penting dan sering menjadi fokus masyarakat internasional. Ideologi terorisme telah menyebar di semua negara di dunia. Pada tahun 2016, masyarakat Indonesia dikejutkan oleh wanita yang akan menjadi kandidat serangan bom bunuh diri. Salah satunya bernama Dian Yulia Novi, wanita pertama yang terlibat dalam aksi teroris dan siap menjadi pembom bunuh diri untuk menyerang Istana Negara Indonesia dengan membawa bom pot dengan daya ledak yang cukup tinggi. Penelitian ini menggunakan metode penelitian kualitatif deskriptif sedangkan jenis penelitiannya menggunakan studi kasus. Kini, Dian menjalani hukuman di Lembaga Pemasyarakatan Perempuan Kelas IIA Bandung. Kasus bom bunuh diri seperti ini jarang terjadi dan perlu pembinaan khusus untuk mengurangi ideologi radikalisme pelakunya. Lembaga Pemasyarakatan dan Badan Penanggulangan Terorisme Nasional menyediakan program reedukasi untuk pembinaannya selama masa pemenjaraannya untuk memberikan pemahaman yang benar tentang Islam dan membuktikan bahwa ideologinya salah. Perkembangan yang telah diperoleh dari program pembinaan adalah ia tidak berusaha menyebarkan pandangannya tentang radikalisme, dan ia bersedia bergaul dengan narapidana kasus lain walaupun hanya dengan orang tertentu.